Clogging of granular materials in silos: effect of gravity and outlet size. Issue 1 (7th October 2015) - Arévalo, Roberto; Zuriguel, Iker
Abstract : By means of extensive numerical simulations we disclose the role of the driving force in the clogging of inert particles passing through a constriction. Abstract : By means of extensive numerical simulations we disclose the role of the driving force in the clogging of inert particles passing through a constriction. We uncover the effect of gravity and outlet size on the flow rate and kinetic energy within the system, and use these quantities to deepen our understanding of the blocking process. First, we confirm the existence of a finite avalanche size when the driving force tends to zero. The magnitude of this limit avalanche size grows with the outlet size, as expected due to geometrical reasons. In addition, there is an augment of the avalanche size when the driving force is increased, an effect that is enhanced by the outlet size. This phenomenology is explained by assuming that in order to get a stable clog developed, two conditions must be fulfilled: (1) an arch spanning the outlet size should be formed; (2) the arch should resist until the complete dissipation of the kinetic energy within the system. From these assumptions, we are able to obtain the probability that an arch gets destabilized, which is shown to primarily depend on the square root of the kinetic energy. A minor additional dependence of the outlet size is also observed which is explained in the light of recent results of the arch resistance in vibrated silos.